BAITUL MAL DALAM SISTEM EKONOMI: Kajian Komparasi Fungsi dengan Bank Sentral dan Kementerian Keuangan - Fitrianto, Achmad Room (El-Qist: Journal of Islamic Economics and Business (JIEB), 2014)
An economy system cannot run smoothly without functions of budgeting and regulating function. Whether it to manage the government spending or to determine the taxes. Both functions was recorded in the early Islamic government. This financial institution known as Baitul Mal. Recently the baitul mal just functioned as not functioned as financial institution that manages the government spending and earning. However if we were have a look back to the Islamic history, baitul mal were functioned as called the ministry of finance and the bank central. History financial institution that manage the government spending and earning exactly look like what the Ministry of finance and The bank Central function. This writing tries to show based on the early Islamic government about the baitul mal function, how it was work, who was in charge and soon. Afterward those functions are compared. In conclusion, the Baitul mal in the early Islamic Government had similar function as the Ministry of finance and the bank Central function on the modern government.